X = 6 , y = -2
hope this helps
Answer:
jniancun
Step-by-step explanation:
bhuybhubujb
dvvwdvwde
dvdv
Step-by-step explanation:
- 3x+5y=7b equation 1
- 2x+4y=1
2x=-4y+1
- x=(-4y+1)/2
- x=(-4y+1)/2 in equation 1
3×(-4y+1)/2+5y=7b
(-12y+3)/2+5y=7b
(-12y+3+10y)/2=7b
(-12y+3)/2=7b
-12y+3=14b
-12y=14b-3
- y=3-14b/12
- y=3-14b/12 in x=(-4y+1)/2
x=(-4×{3-14b/12}+1)/2
x=(-3+14b)/3+1/2
x=14b/3×1/2
Answer:
to put in the value of any variable in this equation(for example 2 ) we will write it as
g(2) = 4(2) - 4(2)^2 + 7(2) -8
g(2) = 8 - 16 + 14 - 8
g(2) = -2
Step-by-step explanation:
Answer:
1) (3 - 6x)(-8) = (-8)(3) - (-8)(6x) = -24 - (-48x) = -24 + 48x = 48x - 24
2) (-12)(2x - 3) = (-12)(2x) - (-12)(3) = -24x - (-36) = -24x + 36 = 36 - 24x
3) (10 - 2x)9 = (9)(10) - (9)(2x) = 90 - 18x
4) (-5)(11x - 2) = (-5)(11x) - (-5)(2) = -55x - (-10) = -55x + 10 = 10 - 55x
5) (1 - 9x)(-10) = (-10)(1) - (-10)(9x) = -10 - (-90x) = -10 + 90x = 90x - 10
6) (-6)(x + 8) = (-6)(x) + (-6)(8) = -6x + (-48) = -6x - 48
7) (-4 + 3x)(-8) = (-8)(-4) + (-8)(3x) = 32 + (-24x) = 32 - 24x
8) (-5)(1 - 11x) = (-5)(1) - (-5)(11x) = -5 - (-55x) = -5 + 55x = 55x -5
9) (-12x + 14)(-5) = (-5)(-12x) + (-5)(14) = 60x + (-70) = 60x - 70
Step-by-step explanation:
The distributive property is a(b + c) = ab + ac